Do Financial Incentives Promote the Employment of the Disabled? - Sher Verick (Institute for the Study of Labor (IZA), 2004)
In October 1999 the unemployment rate of people with severe disabilities in Germany was more than double that of the non-disabled population. To improve this situation, the People with Severe Disabilities Act was reformed to increase incentives for the severely disabled to enter the work force and for employers to hire such workers. In 2003 the Federal Government announced that through this reform it had successfully reduced the number of unemployed by 25% representing around 45,000 individuals. However, an evaluation of the impact of this policy reform on labour market outcomes for the severely disabled indicates that this was not achieved by getting these individuals into employment. Moreover, a recent deterioration in the number of unemployed suggests that the success in 2002 was at best temporary. Thus, there is no evidence that changes to financial incentives in the PSDA had a positive long-term impact on the employment of people with severe disabilities.
Keywords: J23; J22; I18; I12; C13; 330; disability legislation; policy evaluation; labour market outcomes; Schwerbehindertenrecht; Reform; Behinderte Arbeitskräfte; Arbeitsnachfrage; Ökonomischer Anreiz; Wirtschaftspolitische Wirkungsanalyse; Deutschland